Scoping study brief - Potential for adaptation and mitigation - Osumba, Joab J.L.; Recha, John W.M. (2019)
This brief presents the findings of a scoping study on potential for adaptation and mitigation in East Africa, conducted as a requirement for the Climate Resilient Agribusiness for Tomorrow (CRAFT) Project, under Work Stream 3 on Enabling Environment for Climate-Smart Agriculture (CSA). The purpose was to ascertain the potential for adaptation and mitigation under CRAFT.